2021
DOI: 10.1158/1055-9965.epi-20-1126
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 5 Inhibitor Use and Risk of Conventional and Serrated Precursors of Colorectal Cancer

Abstract: Background: Phosphodiesterase 5 (PDE5) inhibitors have been hypothesized to have chemoprotective effects in colorectal cancer. Current population-based epidemiologic evidence is, however, limited and inconsistent. Methods: Among 18,123 men in the Health Professionals Follow-up Study who had at least one lower gastrointestinal endoscopy, we evaluated the association between PDE5 inhibitor use and risk of conventional adenoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Three studies [25, 29, 34] compared sildenafil monotherapy users with nonusers of PDE5 inhibitor. Subgroup analysis did not show an association between sildenafil monotherapy and a lower risk of CRC or advanced colorectal polyps (Figure 6A; OR 0.98, CI 0.79–1.22, p = 0.86, I 2 = 66%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies [25, 29, 34] compared sildenafil monotherapy users with nonusers of PDE5 inhibitor. Subgroup analysis did not show an association between sildenafil monotherapy and a lower risk of CRC or advanced colorectal polyps (Figure 6A; OR 0.98, CI 0.79–1.22, p = 0.86, I 2 = 66%).…”
Section: Resultsmentioning
confidence: 99%
“…Bhagavathula et al [37] reported that users of PDE5 inhibitors had a significantly reduced risk of developing CRC (RR 0.85, CI 0.76–0.95, p = 0.004). However, omission of two relevant studies [22, 29], exclusion of subgroup analysis on primary and secondary prevention and lack of prospective PROSPERO registration of the previous meta‐analysis warranted the conduction of a more comprehensive review on this subject area. The protective effect of PDE5 inhibitors on CRC risk suggested in the present study contrasts with that reported by Soriano et al [36], who found that once the confounder of erectile dysfunction was accounted for no reduced risk of CRC was observed among users of PDE5 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations